Between the short story and the graphic novel: comparative literature and reader education based on ‘The Third Bank of the River’ - Melo, Bruno Santos; Neves, Ana Lúcia Maria de Souza; Sousa, Amasile Coelho Lisboa da Costa (Revista Letras Raras, 2024)
This article presents a comparative analysis between the short story "The Third Bank of the River", by João Guimarães Rosa, and the graphic novel adaptation of the same name, with a script by Maria Helena Rouanet and art by Thaís dos Anjos. The comic is part of the collection of the National School Library Program (PNBE) sent in 2013 to public high schools, thus corresponding to yet another text present in the reading rooms and libraries of schools with the aim of promoting access to culture and encouraging reading. The aim of the study is to reflect on the approach to the canonical literary text from the point of view of dialog with the contemporary language of the comic book (HQ), embarking on literary comparativism and reflection on the relationship between literature and other languages in the formation of the reader. To this end, we revisit current conceptions and critical perspectives on reading, literature, comparative literature and comics, in order to show, through the comparative analysis of different artistic and literary languages, a powerful and thought-provoking reading approach. To this end, we use Bordini and Aguiar (1988), Scliar (2008), Colomer (2007) and Pinheiro (2020) as our theoretical support, with regard to reading, reader education and literary reading in secondary education; Abreu (2006) with regard to the concept of literature as a historical and cultural practice; Carvalhal (2006) on comparative literature and Eisner (2010), Vergueiro (2020) and Ramos (2019) on the language of comics. ; ; ; .